Aanalysis on Impact of Social Media on Human Behaviour Due to Covid Vaccine Tweets - Panjavani, Jatin (International Journal of Computer Sciences and Engineering, 2023)
The Covid-19 outbreak has created a challenge for the whole of mankind and impacted everyday life worldwide. The pandemic had a devastating effect on many people. It also created anxiety, fear, and depression among people. To eradicate the disease, many scientists at major pharmaceutical companies and institutes working together to develop vaccine. Social media is one of the best platforms to discuss the latest trending topics and express your view about them. The Covid-19 Vaccine promotion across the world has created lots of discussion in Twitter, social media platforms where user love to express their feeling and opinion. However, due to lack of knowledge and understanding about Covid – 19 vaccines, it has created negative sentiments towards vaccine among few. Also, there has not been much research work done on in-depth analysis of people’s opinion or sentiment towards various vaccine and its brands. In this study will be using publicly available Covid-19 vaccine tweets to understand public opinion or feeling about various covid-19 vaccine brands. This research will be using publicly available Covid-19 vaccine tweets to understand public opinion or feeling about various Covid-19 vaccine brands. The study was conducted using publicly available datasets from online resource, Kaggle. The dataset contains 228207 tweets from Kaggle about the opinion for Covid-19 vaccines during 12 December 2020 to 24 November 2021. After the extraction, vaccine sentiments identified across all brands. After identification of sentiments, accuracy be evaluated based on prediction using various metrics. This research will find the difference in public opinion on Covid-19 vaccines. Understanding the sentiments and public opinions towards vaccine will help health agencies to increase positive awareness about covid-19 vaccine across world.